Factor influence whistle blowing intentions at Selangor immigration department / Nur Yuskhalida Mohd Yusri - Mohd Yusri, Nur Yuskhalida (2019)
For recent years, integrity value has been favarouble in Malaysia especially in government sector as Prime Minister, Tun Dr Mahathir always emphasize that civil servants must ensure performing the task with integrity value. This because, public sector brings the name of government in delivering the service. Thus, government wants to ensure that there is clean in administration to gain the trust of citizens. However, still a lot of misconduct such as bribe, fraud and misuse of power occur in public sector which this had cause bad name of government as well as loss for the organization. In addition, whistle blowing is the medium in order to report the wrongdoing. Moreover, government had implemented Whistleblower Protection Act 2010 to encourage whistle blower as this Act will protect the identity of the whistleblower. The needs of this Act are to ensure whistleblower does not have to be afraid disclose the wrongdoing. This study was conducted to investigate the factor influence whistle blowing intention and role of job level towards whistle blowing intention at Selangor Immigration Department as Immigration Department and Selangor state receive the highest number of complaints as stated by Enforcement Agency Integrity Commission. 172 respondents participated for this study which resulted, the three factor which is organizational commitment, ethical climate and seriousness of wrongdoing has relationship with whistle blowing intention. However, there is no difference between groups of job level towards whistle blowing intention.